2018
DOI: 10.1007/s00410-018-1482-1
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the prograde P–T path of Precambrian eclogite using Ti-in-quartz and Zr-in-rutile geothermobarometry

Abstract: A Fe-Ti-rich garnet, clinopyroxene, and quartz eclogite sample from the 1.0 Ga Sveconorwegian orogen, SW Sweden, contains abundant quartz, rutile, and zircon in distinct micro-textural sites: garnet core, garnet rim, and matrix, constituting an ideal case for investigation of the behavior of Zr-in-rutile and Ti-in-quartz at high-pressure and temperature. A P-T path, peaking at 16.5-19 kbar and 850-900 °C, has been constrained independently for the same rock by pseudosection modelling; input pressures from this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 41 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…For the first case, despite not abundant, small grained rutile has been found in the cores of garnet porphyroblasts from different eclogites, and a few of them are intergrowth with or near calcic amphibole grains (Figure S2 in Supporting Information ), suggesting they have high potential to achieve chemical equilibrium during growth of calcic amphibole and temperature calculated by Ti‐in‐calcic amphibole thermometer is reliable. For the second case, previous studies have proven that the Zr content of rutile inclusions in garnet could survive from later heating and that a Zr‐in‐rutile thermometer based on rutile inclusions in garnet grains could robustly reflect the nucleation temperature of garnet even if the peak condition reaches ultrahigh temperature (e.g., Schantl et al., 2019; Tual et al., 2018). This suggests that the temperature recorded by rutile inclusion is robust.…”
Section: Discussionmentioning
confidence: 99%
“…For the first case, despite not abundant, small grained rutile has been found in the cores of garnet porphyroblasts from different eclogites, and a few of them are intergrowth with or near calcic amphibole grains (Figure S2 in Supporting Information ), suggesting they have high potential to achieve chemical equilibrium during growth of calcic amphibole and temperature calculated by Ti‐in‐calcic amphibole thermometer is reliable. For the second case, previous studies have proven that the Zr content of rutile inclusions in garnet could survive from later heating and that a Zr‐in‐rutile thermometer based on rutile inclusions in garnet grains could robustly reflect the nucleation temperature of garnet even if the peak condition reaches ultrahigh temperature (e.g., Schantl et al., 2019; Tual et al., 2018). This suggests that the temperature recorded by rutile inclusion is robust.…”
Section: Discussionmentioning
confidence: 99%
“…The Zr partitioning and diffusion in rutile have been experimentally constrained (Cherniak et al, 2007; Ferry & Watson, 2007; Tomkins et al, 2007; Zack, Moraes, et al, 2004); however, controversy still exists regarding Zr diffusion rates (Blackburn et al, 2012; Cherniak et al, 2007; Ewing et al, 2013; Kooijman et al, 2012; Luvizotto & Zack, 2009; Meyer et al, 2011; Pape et al, 2016; Taylor‐Jones & Powell, 2015; Zack, Moraes, et al, 2004). Cherniak et al (2007) have shown that rutile is only moderately retentive for Zr, whereas geological studies indicate preservation of Zr‐in rutile cores even at UHT (Ewing et al, 2013; Kooijman et al, 2012; Pape et al, 2016; Tual et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion entrapment P-T conditions are additionally constrained by the crossing point of quartz-in-garnet isomekes and Ti-in-quartz isoplets, which serve as an independent thermometer to validate zircon-in-garnet elastic thermometry. The application of Ti-in-quartz geothermometer is a common method used to obtain P-T estimates of crystallization as quartz occurs in most crustal rocks over a wide range of P-T conditions (e.g., Thomas et al, 2010;Tual et al, 2018). Recently, it has been successfully applied not only on matrix quartz, but on inclusions trapped in garnet (Gonzalez et al, 2019).…”
Section: Application Of Elastic Thermobarometry Coupled With Trace El...mentioning
confidence: 99%